International economic integration : limits and prospects - Jovanovic, Miroslav N., 1957- (London ; New York : Routledge, 1998)
This new edition reflects current developments in international economic integration. The work includes an expanded chapter on the Common Market which covers new developments in capital mobility and industrial policy.
1. Introduction -- 2. Customs Union -- 3. Common Market -- 4. Economic Union -- 5. Integration Schemes -- 6. Measurement of the Effects of International Economic Integration -- 7. Conclusion -- Annex I. GATT: Regional integration agreements -- Annex II. Council for Mutual Economic Assistance -- Annex III. Eastern enlargement of the European Union -- Annex IV. Research topics for the future.
Includes bibliographical references (. [417]-437) and index.
Keywords: International economic integration; International economic integration